Chap 5 Algebra: 6 A.M. QUIZ (23 May 2010) (I)

Simplify (with complete working)

a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)

Note: This is a 2-mark question.

9 comments:

  1. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    = (aa + ax) - (bc + bx) - (ca + cx) + (ac - ax) +
    (cb + cx)
    = aa - bc - bx - ca - cx + ac + cb + cx
    = aa - bx - ca - cx + ac + cx
    = aa - bx - ca + ac
    = aa - bx

    ReplyDelete
  2. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    = (aa + ax) - (bc + bx) - (ca + cx) + (ac - ax) + (cb + cx)
    = aa + ax - bc - bx - ca - cx + ac - ax + cb +cx
    = aa + (ax - ax) + (bc - cb) + (ac - ca) + (cx - cx) - bx
    = aa + 0 + 0 + 0 + 0 - bx
    = aa - bx

    JJ(:

    ReplyDelete
  3. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    = (aa + ax) - (bc + bx) - (ca + cx) + (ac - ax) +
    (cb + cx)
    = aa - bc - bx - ca - cx + ac + cb + cx
    = aa - bx - ca - cx + ac + cx
    = aa - bx - ca + ac
    = aa - bx

    ReplyDelete
  4. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    = (aa + ax) - (bc + bx) - (ca + cx) + (ac - ax) +
    (cb + cx)
    = aa - bc - bx - ca - cx + ac + cb + cx
    = aa - bx - ca - cx + ac + cx
    = aa - bx - ca + ac
    = aa - bx

    ReplyDelete
  5. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    = (a x a + a x x)- (b x c + b x x) - (c x a + c x x) + (a x c - x x a) + (c x b + x x c)
    = aa + ax - bc + bx - ca + cx + ac - ax + cb + cx
    =aa+ ( ax - ax) + (-bc + bc) - bx - (ca + ac) +(-cx+cx)
    =aa - bx

    ReplyDelete
  6. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    =a^2+ax - bc- bx - ca - cx + ac - ax + cb +cx
    =a^2+ax-ax-bc+cb-ca+ac-cx+cx-bx
    =a^2-bc+cb-ca+ac-cx+cx-bx
    =a^2-ca+ac-cx+cx-bx
    =a^2-cx+cx-bx
    =a^2-bx

    ReplyDelete
  7. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    =a^2 +ax -bc -bx -ac -cx +ac -cx +ac -ax +bc +cx
    =a^2 +ax -ax -bc +bc -bx -ac +ac -cx +cx
    =a^2 -bx

    ReplyDelete
  8. a(a + x) - b(c + x) - c(a + x) + a(c - x) + c(b + x)
    =(aa+ax)-(bc+bx)-(ca+cx)+(ac-ax)+(cb+cx)
    =aa+ax-bc-bx-ca-cx+ac-ax+cb+cx
    =aa-bx

    ReplyDelete
  9. This comment has been removed by the author.

    ReplyDelete